Psychopathic Profiles in the General Population: Construction and validation of the ERPO Scale - García-Fernández, Jaime; González-Nuevo, Covadonga; Postigo, Álvaro; Menéndez-Aller, Álvaro; García-Cueto, Eduardo; Cuesta, Marcelino (Anales de Psicología / Annals of Psychology, 2026)
Subclinical psychopathy is an issue of interest for various psychological fields (human resources, forensic context, clinical psychology, etc.). The aim of this study was to construct a scale for the assessment of subclinical psychopathy and to use it to obtain psychopathic profiles in the general adult Spanish population. To achieve this, a set of items evaluating 3 dimensions (Manipulation, Insensitivity, Reckless Impulsivity) was generated and reviewed by a panel of experts in psychometrics and psychological assessment. The pilot study was completed by 436 subjects, and the main study by 536. The internal structure of the scale was explored using various Exploratory Factor Analyses and a final Confirmatory Factor Analysis. Cluster analysis resulted in 5 subject groupings (Psychopathic, Non-Psychopathic, Manipulative, Callous, and Reckless), which showed differential relationships with Psychopathy, Dark Triad, Agreeableness, Honesty-Humility, and Self-Interest. The developed scale provides valid and reliable scores for assessing subclinical psychopathy in the general adult Spanish population, as well as the possibility of establishing 5 psychopathic profiles in this population.